RANCANG BANGUN PROTOTIPE GARDU PEMBANGKIT LISTRIK HYBRID MIKRO HIDRO DAN SEL SURYA SEBAGAI MEDIA PEMBELAJARAN PRAKTIKUM TEKNIK ELEKTRO - ., Sugeng; Rokhman, Taufiqur; ., Paridawati; Sofwan, Agus (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2018)
In the Department of Electrical Engineering,Islamic University "45" Bekasiuntil now does not have a laboratory of Renewable energy. In this research, a hybrid power plants have been designed by combined between hydroelectric power plants and solar power plants.From the design result of the Solar Cell Power Plant, obtained that for 1 to 4 pieces of 100 Wp solar panels obtained the generation voltage of 21.12 volts generating power of 18.80 Watts on average time for 7.8 hours. Whereas for MHP the average voltage is 10.81 Volt and the generation power is 41.48 Watts for 8 hours of use.